Targeting Glioma Cells with Nutraceuticals: Therapeutic Effects Based on Molecular Mechanisms, New Evidence and Perspectives - Salami, Marziyeh; Salami, Raziyeh; Aarabi, Mohammad-Hossein; Mafi, Alireza; Ghorbanhosseini, Seyedeh S.; Shafabakhsh, Rana; Asemi, Zatollah (Mini Reviews in Medicinal Chemistry, 2023)
Gliomas are the most common malignant cancers of the brain that have unregulated proliferation and are known as highly invasive tumors. Hence, their relapse rate is high, and the prognosis is low. Despite remarkable advances in neuroimaging, neurosurgery, and radiation therapy, they, especially glioblastoma, are highly resistant to treatments, including radiotherapy, surgery, and temozolomide chemotherapy. The average survival rate for patients with malignant glioma is still less than two years. Accordingly, the search for new treatment options has recently become an urgent need. Today, a number of nutraceuticals have been considered because of their special role in inhibiting the angiogenic process, metastasis, and apoptosis, resulting in the inhibition of tumor growth, including glioma. Nutraceuticals can disrupt cancer cells by affecting different pathways. In fact, these compounds can reduce the growth of cancer cells, inhibit their proliferation and angiogenesis, as well as induce apoptosis in these cells and play an important role in various stages of treatment. One of the key targets of nutraceuticals may be to regulate cellular signaling pathways, such as PI3K/Akt/mTORC1, JAK/STAT, and GSK-3, or to exert their effects through other mechanisms, such as cytokine receptors and inflammatory pathways, reactive oxygen species, and miRNAs. This review refers to the results of recent studies and target molecules as well as signaling pathways affected by some nutraceuticals in glioma cells. These studies indicated that clinical trials are imminent and new approaches can be beneficial for patients.
Keywords: signaling pathway